Quando cães, humanos e ruas se encontram: pensamento, movimento, movimento e sensação entre vidas, afetos, arte e palavras - Gonçalves, Michele Fernandes (2016)
This work attempts to the encounter between humans, dogs and streets. The focus is to explore the power of the relationships established among these entities, in the public space, when they meet each other and their homes through art. The goal is to affirm the existence and permanence of dogs on the streets and evoke the production of new feelings and sensitive connections between humans and them. The exhaustion of the thought about some prevailing notions on the distinctions among entities, and also the opening to the sensations and affections evoked when dogs and humans meet each other, on the streets, through art and words, serve to the questioning of the relationships between them and their homes, and also to a resizing effort on those relations, enabling the vision of the stray dogs status as beyond the categories of abandonment and suffering. The methodology is the cartography, as proposed by Gilles Deleuze e Félix Guattari, which takes in the experimentation of the thinking, trying to realize the dynamics, fluxes and intensities of the objects and assuming that the thinking and the knowledge production starts always from multiple connections. In the field of the theory, we performed a bibliographic research on contemporary authors of anthropology, philosophy, psychoanalysis and the arts as a way to resume and shuffle some concepts and also make other means and viewpoints possible for the relationships among entities. In the field of the praxis, the fieldwork involved some walking with the stray dogs in the city of Sorocaba. We also produced some narratives taking the fieldwork as inspirations, and some wheat-paste urban interventions, both as a way to create powerful encounters between humans and dogs on the streets where they come across to each other.